Epidemiology and clinical characteristics of biopsy-confirmed adult-onset IgA vasculitis in southern Sweden - David Jayne; Mårten Segelmark; Aladdin J Mohammad; Karl Gisslander; Michaela Thalen; Jacob Sode (RMD Open)
Objective Immunoglobulin A vasculitis (IgAV) is the most prevalent primary childhood vasculitis in Sweden, but is considerably rarer in adults. This study aims to describe the epidemiology, clinical characteristics and renal outcome of adult-onset IgAV in Skåne, Sweden.Methods The study area consisted of Skåne, the southernmost region of Sweden, with a population ≥18 years of 990 464 on 31 December 2010. Adult patients assigned the International Classification of Diseases-10 code for IgAV (D69.0) from 2000 through 2019 were retrospectively identified in a population-based database. Medical records were reviewed to validate the diagnosis of IgAV and extract data. Only patients with clinical manifestations of IgAV and biopsy-confirmed disease were included. The annual incidence and point prevalence of biopsy-confirmed IgAV were estimated.Results Fifty-nine patients (19 women) were classified as having adult-onset IgAV. The incidence was 3 per 1 000 000 and was higher among men than women (4 vs 2/1 000 000, p=0.004). Ninety-seven per cent of patients presented with non-thrombocytopenic purpura, 78% with renal involvement, 59% with arthritis/arthralgia and 39% with gastrointestinal symptoms. Fifteen per cent developed chronic kidney disease stage ≥G3 a and one patient progressed to end-stage kidney disease during follow-up.Conclusion Adult-onset IgAV is rare in southern Sweden with the incidence higher in men than in women. IgAV frequently affects the kidneys and leads to chronic kidney disease in adults, although the long-term renal outcome appears favourable compared with other small-vessel vasculitides affecting the kidneys.